A Case of Familial Hemophagocytic Lymphohistiocytosis Type 4 With Involvement of the Central Nervous System Complicated With Infarct. Issue 6 (August 2017) - Ciraci, Saliha; Ozcan, Alper; Ozdemir, Mustafa M.; Chiang, Samuel C.C.; Tesi, Bianca; Ozdemir, Akif M.; Karakukcu, Musa; Patiroglu, Turkan; Acipayam, Can; Doganay, Selim; Gumus, Hakan; Unal, Ekrem
Abstract : Background: Familial hemophagocytic lymphohistiocytosis (HLH) is a fatal disease affecting infants and very young children. Central nervous system involvement of HLH can cause catastrophic results. Method: We present a case with cranial involvement of familial HLH type 4 who showed diffuse infiltration of white matter complicated with intracranial thrombosis. A 5-year-old girl from a consanguineous couple presented with fever and pancytopenia, and was referred to our hematology unit. Examination revealed fever, lymphadenopathy, and hepatosplenomegaly. Ultrasound examination revealed hepatosplenomegaly and free intra-abdominal fluid. HLH was revealed on bone marrow aspiration biopsy. Defective natural killer and T lymphocyte cytotoxicity using degranulation tests was determined. In the genetic analysis, syntaxin gene mutation was found. On T2-weighted and T2-fluid-attenuated inversion recovery magnetic resonance imaging (MRI), diffuse hyperintense signal changes of cerebral white matter, indicating white matter demyelination, were observed. A second brain MRI showed an acute infarct involving the left temporooccipital region. Immunosuppressive therapy according to the HLH 2004 protocol was started. The infarct resolved but white matter lesions were stable on the brain MRI that was performed 1 month later. Brain MRI taken 4 months after the first examination showed stable cerebral white matter lesions, but hyperintense signal changes appeared in the cerebellar white matter and were regarded as progression. The patient died because of infection despite immunosuppressive therapy. Conclusions: Physicians managing patients with HLH must be vigilant about the possibility of central nervous system involvement including stroke.